2018
DOI: 10.5546/aap.2018.eng.e75
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in pediatric clinical practice

Abstract: Vitamin D research suggests it has a role in disorders other than bone metabolism. Objective: To update the information on vitamin D deficiency (VDD) in pediatric clinical disorders. Methods: Search in virtual libraries, giving priority to clinical and longitudinal studies and meta-analyses on VDD in the pediatric age group published in the past 20 years. The terms "vitamin D deficiency", "children and adolescents" (both in Spanish and English) were used as search descriptors. Results:In the pediatric populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…Additional potential adverse outcomes of furosemide use in premature infants include metabolic bone disease (osteopenia) of prematurity and electrolyte abnormalities related to urinary loss of sodium, chloride, and calcium [ 53 55 ]. As with other adverse outcomes, the etiology of metabolic bone disease in premature infants likely has many causes, and infants with severe illness often have multiple risk factors such as insufficient phosphorus intake, vitamin D deficiency, prolonged immobilization, mechanical ventilation, and exposure to steroids and antibiotics [ 56 58 ]. However, there is a lack of consensus on the definition of metabolic bone disease of prematurity, with some definitions relying on serum mineral levels and others based on radiographical findings [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional potential adverse outcomes of furosemide use in premature infants include metabolic bone disease (osteopenia) of prematurity and electrolyte abnormalities related to urinary loss of sodium, chloride, and calcium [ 53 55 ]. As with other adverse outcomes, the etiology of metabolic bone disease in premature infants likely has many causes, and infants with severe illness often have multiple risk factors such as insufficient phosphorus intake, vitamin D deficiency, prolonged immobilization, mechanical ventilation, and exposure to steroids and antibiotics [ 56 58 ]. However, there is a lack of consensus on the definition of metabolic bone disease of prematurity, with some definitions relying on serum mineral levels and others based on radiographical findings [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is a key factor in the regulation of bone mineralization and calcium homeostasis in both genders. Vitamin D deficiency is widespread worldwide [ 23 ]. A recent study has confirmed that vitamin D receptors are widely present in ovary, testis, pituitary, hypothalamus, and the reproductive system is one of the target organs of vitamin D, indicating that vitamin D may be involved in the regulation of gonadal function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in vitamin D and its properties has increased significantly over the past two decades. Numerous studies conducted in various regions of the world indicate that vitamin D deficiencies occur in all countries, regardless of the latitude and age [15][16][17][18]. This is also true for Polish children.…”
Section: Discussionmentioning
confidence: 99%